Pengaruh Latihan Power Otot Tungkai terhadap Keterampilan Passing pada Permainan Sepak Bola di SSB Bima Muda Disdikbud - Taufiq Iqsal Afandi; Daryono Daryono; Hengki Kumbara (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Based on observations and the latest information, when researchers took part in training with SSB Bima Muda Disdikbud, the athletes looked very weak when passing and not optimal. This problem is caused by the leg muscle power not being optimal. So it is necessary to carry out exercises to increase leg muscle power for passing skills. The research method used is an experimental one group pre-test post-test design, which is carried out by providing treatment to research subjects. This research, which involved 21 SSB Bima Muda Disdikbud athletes with 16 treatments in the form of leg muscle power training, gave results where the average passing before was 66.5 which changed to 84.8 after being given the leg muscle power training treatment. Meanwhile, the results of the paired sample t-test show that there is an influence of leg muscle power training on the passing skills of SSB Bima Muda Disdikbud athletes because the sig. (2-tailed) is 0.05. Meanwhile ttable at α 0.05 Df = N-1 where (DF = 21 -1 = 20) so that ttable is obtained with a value of 1.725. So this research meets the requirements where tcount > ttable (13,005 > 1.725) thus Ha is accepted and it can be concluded that there is an influence of leg muscle power training on passing skills in the soccer game of SSB Bima Muda Disdikbud athletes.